Formulation, Characterization, Antibacterial Activity, Antioxidant Activity, and Safety Evaluation of Camphora longepaniculata Essential Oil Nanoemulsions Through High-Pressure Homogenization - Yue Yan; Changhe Wei; Xin Liu; Xin Zhao; Shanmei Zhao; Shuai Tong; Guoyou Ren; Qin Wei (Antioxidants)
The volatility, instability, and water insolubility of Camphora longepaniculata essential oil (CLEO) limit its practical applications in the food, pharmaceutical, and cosmetics industries. CLEO nanoemulsions (CLNEs) were formulated and characterized to overcome the aforementioned issues. The volatile compounds of CLEO were identified by gas chromatography–mass spectrometry. CLNEs were prepared using EL-40 (5%, w/w) as the surfactant via the high-pressure homogenization method. The formation of nanoemulsions was verified by Fourier transform infrared spectroscopy and transmission electron microscopy. Homogenized nanoemulsions had smaller particle sizes of 39.99 ± 0.47 nm and exhibited enhanced stability. The nanostructured CLEO showed an antibacterial effect against Escherichia coli and Staphylococcus aureus. The antibacterial mechanism was explored through bacterial morphology and intracellular lysate leakage. CLNEs disrupted the structure of bacterial cells and impaired the permeability of cell membranes, resulting in the leakage of bacterial intracellular contents. The nanoemulsions exhibited superior radical scavenging ability compared to the pure oil. Furthermore, evaluations of the cellular safety of the CLNEs demonstrated that the survival rate of exposed HOECs was greater than 90%, with an apoptosis rate of less than 10% in a concentration range. The results demonstrated that nanoemulsification improved the stability, solubility in aqueous media, and bioavailability of CLEO, thereby broadening its potential industrial applications as a natural antibacterial and antioxidant agent.